Analytical investigation of nonlinear dynamics of soliton transmission in discrete system under self-induced regime - Mohd Busul Aklan, Nor Amirah; Samiun, Anis Sulaikha; Umarov, Bakhram (MMU Press, 2025)
This study investigates the soliton propagation in a one-dimensional discrete system characterized by the Discrete Nonlinear Schrödinger Equation (DNLSE). The DNLSE is a fundamental model in wave phenomena, encompassing a broad spectrum of physical systems ranging from optics to fluid dynamics. The analytical study employs the variational approximation (VA) method to thoroughly examine the process and essential parameters governing soliton evolutions, such as width, center-of-mass position, and linear and quadratic phase-front corrections are determined and graphically interpreted. The results show that an increase in linear phase-front correction corresponds to an increase in both the soliton’s initial velocity and propagation distance